Ludwig’s angina - an emergency complication arising from delayed dental treatment: The experience in a Nigerian tertiary institution - Thomas Owobu; Edugie Ekuase; Oba O. Azah; Sulaiman S. Adamu; Babatunde O. Bamgbose (Journal of Dentomaxillofacial Science, 2020)
Objective: The aim of this paper was to report two cases and management of Ludwig’s angina in a Nigerian tertiary health facilty.Methods: Ludwig’s angina is an acute onset, potentially life-threatening surgical emergency in young adults that presents with rapidly expanding, diffuse inflammation of the submandibular and sublingual spaces, mostly from odontogenic infections.Results: One of the sequelae is airway compromise. Given the sparse health facilities and poor access to health, we observed an increasing rate of Ludwig’s angina secondary to odontogenic infections in our practice. We present two cases of Ludwig’s Angina arising from delayed dental treatment.Conclusion: Socioeconomic status and unrest due to insurgency have hampered early presentation and management